Regulation of the Immune Response by the Inflammatory Metabolic Microenvironment in the Context of Allotransplantation - Degauque, Nicolas; Brosseau, Carole; Brouard, Sophie (Frontiers in Immunology, 2018)
Antigen challenge induced by allotransplantation results in the activation of T and B cells, followed by their differentiation and proliferation to mount an effective immune response. Metabolic fitness has been shown to be crucial for supporting the major shift from quiescent to active immune cells and for tuning the immune response. Metabolic reprogramming includes regulation of the balance between glycolysis and mitochondrial respiration processes. Recent research has shed new light on the functions served by the end products of metabolism such as lactate, acetate and ATP. At enhanced local concentrations, these metabolites have complex effects in which they not only induce T and B cell responses, cell mobility and cytokine secretion but also favor the resolution of inflammation by promoting regulatory functions. Such mechanisms are instrumental in the context of the immune response in transplantation, not only to protect the graft and/or eliminate cells targeting it but also to maintain cell homeostasis per se. Metabolic adaptation thus plays an instrumental role on the outcome of the cellular and humoral responses. This, of course, raises the possibility of drugs that would interfere in these metabolic pathways to control the immune response but also highlights the risk that some drugs may perturb this metabolism and cell homeostasis and be deleterious for graft outcome. This review focuses on how metabolic alterations of the local immune microenvironment regulate the immune response and the impact of metabolic manipulation in allotransplantation.